2023
DOI: 10.1093/bib/bbad202
|View full text |Cite
|
Sign up to set email alerts
|

MITNet: a fusion transformer and convolutional neural network architecture approach for T-cell epitope prediction

Abstract: Classifying epitopes is essential since they can be applied in various fields, including therapeutics, diagnostics and peptide-based vaccines. To determine the epitope or peptide against an antibody, epitope mapping with peptides is the most extensively used method. However, this method is more time-consuming and inefficient than using present methods. The ability to retrieve data on protein sequences through laboratory procedures has led to the development of computational models that predict epitope binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…With the increasing availability of TCR and epitope sequencing data from high-throughput sequencing techniques in publicly available data resources (Jokinen et al, 2021), AI and ML approaches have been able to be used to predict TCR CDR3β binding to epitopes presented by MHC class 1 (MHC-I) (Hudson et al, 2023). These tools apply methods ranging from relatively simple ML models such as Random Forest and clustering (Chronister et al, 2021; Dash et al, 2017; Jokinen et al, 2021; Pham et al, 2023) to various forms of deep learning-based AI techniques, including convolutional and recurrent neural networks (Bravi et al, 2023; Cai et al, 2022; Darmawan et al, 2023; Gao, Gao, Li, et al, 2023; Jiang et al, 2023; Jokinen et al, 2023; Myronov et al, 2023; D. Wang et al, 2023; Z.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing availability of TCR and epitope sequencing data from high-throughput sequencing techniques in publicly available data resources (Jokinen et al, 2021), AI and ML approaches have been able to be used to predict TCR CDR3β binding to epitopes presented by MHC class 1 (MHC-I) (Hudson et al, 2023). These tools apply methods ranging from relatively simple ML models such as Random Forest and clustering (Chronister et al, 2021; Dash et al, 2017; Jokinen et al, 2021; Pham et al, 2023) to various forms of deep learning-based AI techniques, including convolutional and recurrent neural networks (Bravi et al, 2023; Cai et al, 2022; Darmawan et al, 2023; Gao, Gao, Li, et al, 2023; Jiang et al, 2023; Jokinen et al, 2023; Myronov et al, 2023; D. Wang et al, 2023; Z.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has also been shown that the use of features that lend themselves to ML models leads to better performance in TCR specificity prediction (Pham et al, 2023). Most ML models have been sequence-based, encoding sequences using either the BLOSUM substitution matrix (Cai et al, 2022; Darmawan et al, 2023; Gao, Gao, Li, et al, 2023; Pham et al, 2023) and/or Atchley factors(Atchley et al, 2005). The BLOSUM matrix applies a score for amino-acid substitutions while Atchley factors are multidimensional, composite features for each amino acid derived using unsupervised ML on primarily physicochemical features (Jiang et al, 2023; Lu et al, 2021; Moris et al, 2021).…”
Section: Introductionmentioning
confidence: 99%